The Impact of Banking Competition on Bank Financial Stability: Evidence from ASEAN 5 Countries - Mahjus Ekananda (Faculty of Economic and Business, 2023)
In the era of the global economy, increasing banking competition will encourage an increase in banking transactions and activities. Banking transactions and activities will affect a country's financial stability. The purpose is to obtain the nonlinear effect of banking competition on financial stability at a specific regime. Previous research assumed that this impact applies to every economic regime. The impact of banking competition on financial stability can change at certain regime levels. Nonlinear impact occurs according to the regime. The method is based on a nonlinear threshold regression model. The researchers obtained the data from five ASEAN countries. The findings of this research are in-depth information about the financial system stability model. Analysis of the effect of variance supports the inconsistency of the effects found by several previous researchers. Practical implications are aimed at policymakers to make different decisions at the GDP level, CAR and Liquidity. The economic regime in each country is different, so this analysis is constructive for policymakers to see the conditions of banking competition and financial system stability at a certain regime level. The originality article systematically offers an analysis that assumes the effect can change at a certain regime level.JEL Classification: E5, G15, G01, G32, C24How to Cite:Ekananda, M. (2023). The Impact of Banking Competition on Bank Financial Stability: Evidence from ASEAN 5 Countries. Etikonomi, 22(2), 409 – 428. https://doi.org/10.15408/etk.v22i2.31003.